A Decade of Innovation: A Bibliometric Analysis of Advergames and Gamification in Tourist Destinations - Islam Abusharieh; Carla Ruiz Mafe; Inés Küster (Journal of Theoretical and Applied Electronic Commerce Research)
This study presents a comprehensive bibliometric analysis of the research landscape surrounding advergames and gamification in tourist destinations over the past decade. By analyzing 623 scholarly publications indexed in the Web of Science (WoS) database, this study identifies key trends, thematic clusters, influential authors, and collaborative networks within this interdisciplinary field. The findings highlight the growing importance of digital innovations in tourism marketing, particularly using gamification to enhance tourist experiences, promote cultural and heritage sites, and support sustainable tourism practices. The study also underscores the global nature of research in this area, with significant contributions from leading countries and the emergence of new research centers. The analysis provides valuable theoretical and practical insights, offering actionable recommendations for tourism marketers, destination managers, and policymakers on leveraging advergames and gamification to achieve strategic objectives. Despite its contributions, this study acknowledges limitations, such as the reliance on a single database and the need for more qualitative analyses. It suggests several avenues for future research to advance the field further.